Comparative analysis on toroidal fins with variable thickness rectangular splines for heat transfer enhancement - Krishna, K Hari; Rao, M Koteswara; Kumar, K Sai Pavan; Kranti, Alajangi; Atgur, Vinay; Manavendra, G (International Journal of Engineering and Technology, 2018)
In the present situation, there is a need for devices to carry the thermal energy generated in the system. Fins are the efficient devices which are going to carry the heat generated in the system. In the present work, we have chosen a special shape of fins by choosing two different materials. Toroidal fins have been considered. By varying its shapes heat transfer analysis has been carried out. In the present work, we have considered the toroidal fins having Aluminium and Gunmetal materials. The thicknesses of the spline are reduced from 7 mm to 3mm. The effectiveness for Aluminium 3mm is 3.28 and for 7mm is 3.3723. The effectiveness of Gun metal 3mm is 2.02 and for 7mm is 2.7895.